2017
DOI: 10.1007/s00394-017-1547-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rice, pea and oat proteins in attenuating glycemic response of sugar-sweetened beverages

Abstract: Plant proteins altered the glycemic and appetitive responses of Asian males to a sugar-sweetened beverage. Food-based interventions are useful in promoting glycemic control. This trial was registered with ClinicalTrials.gov as NCT02933424.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 50 publications
2
29
3
Order By: Relevance
“…Besides the stimulation of insulin secretion (driven by direct stimulatory effects, but also indirectly, through an increased incretin response), underlying pathways include delayed gastric emptying under the influence of the same incretin hormones [ 62 ]. Whey or soy proteins seem to give the best responses [ 8 , 63 ], but favourable effects on postprandial glycemic levels were also reported for rice, pea, and oat proteins [ 64 ]. Giezenaar et al found whey protein drinks to slow gastric emptying and alter insulin, glucagon, GLP-1, and GIP secretions in older men and women [ 65 ].…”
Section: Influence Of Nutrients On Gastric Emptying and Glycemic Lmentioning
confidence: 99%
“…Besides the stimulation of insulin secretion (driven by direct stimulatory effects, but also indirectly, through an increased incretin response), underlying pathways include delayed gastric emptying under the influence of the same incretin hormones [ 62 ]. Whey or soy proteins seem to give the best responses [ 8 , 63 ], but favourable effects on postprandial glycemic levels were also reported for rice, pea, and oat proteins [ 64 ]. Giezenaar et al found whey protein drinks to slow gastric emptying and alter insulin, glucagon, GLP-1, and GIP secretions in older men and women [ 65 ].…”
Section: Influence Of Nutrients On Gastric Emptying and Glycemic Lmentioning
confidence: 99%
“…In a series of studies that contained plant proteins dispensed as beverages, it has repeatedly been demonstrated that these proteins are insulinotropic and are therefore effective in reducing the glycemic response of foods [ 10 , 11 , 24 ]. The average amount of proteins in these beverages has been in the region of 12–24 g. In our present study, we have demonstrated that compared to 7.8 g of protein, a considerable reduction in the soy protein content (3.4 g) of a beverage but the inclusion of rice bran can elicit a similar reduction in the glycemic response.…”
Section: Discussionmentioning
confidence: 99%
“…The glycemic index (GI) is a classification of the blood glucose-raising potential of carbohydrate foods, and there is substantial evidence suggesting that the consumption of low GI foods decreases post-prandial blood glucose and its insulin levels and fluctuations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In recent years, studies have shown that adding fat, fiber, and plant and animal protein to carbohydrate meals can lower the glycemic response [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of trials identified in the search referred to the effects of plant proteins on postprandial concentrations of blood glucose, insulin and appetite regulating hormones [40][41][42]45,[49][50][51][52][53][54][57][58][59][60][61][62][63]65] (Table 3). The most frequently reported proteins in this context were pea proteins [40,41,45,[49][50][51][52]54,57,58,[61][62][63], followed by fava bean [42,59], rice [51,62], lupin [61,65], oats [62], lentil [53] and hemp [60]. The dosage of protein was reported in two formats: absolute values (g/day) or in g per kg of body weight.…”
Section: Satiety Glycemic and Insulinemic Responsesmentioning
confidence: 99%